An Examination of Mathematics Teacher Candidates’ Definitions and Images of the Fraction Concept - Tuğçe Çınargil; Muhammed Özsoy; Gülçin Oflaz (Uluslararası Türk Eğitim Bilimleri Dergisi)
This study aims to examine the definitions and images of the concept of fractions held by mathematics teacher candidates. However, the aim has been to reveal the similarities or differences in the definitions and images of fractions held by teacher candidates throughout the different stages of the program. A basic qualitative research design has been used in the study. The study group consists of 155 mathematics teacher candidates studying in the mathematics teaching program of a state university in the Central Anatolia Region for the 2023-2024 academic year, selected using the maximum diversity sampling method. A form consisting of open-ended questions has been used as a data collection tool. Descriptive analysis was used in the analysis of teacher candidates' definitions and images related to the concept of fractions. According to the findings of the study, the explanations provided by teacher candidates regarding the definition of fractions have been categorized under four themes: meanings of fractions, types of fractions, association with rational numbers, and elements of fractions. When examining the drawings of teacher candidates regarding the concept of fractions, it has been observed that images of part-whole, sharing, ratio, set, operator, association, and number line have emerged. Teacher candidates have mostly made definitions using the meanings of fractions, with the part-whole meaning being the most frequently used among them. Additionally, it has been addressed how the definitions and images of the concept of fractions change according to the grade levels of the teacher candidates.